Nekateri pomisleki ob uvajanju pogajanj o priznanju krivde v slovenski kazenski postopek - Tratnik Zagorac, Andreja (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2011)
One of the main features of the latest proposed amendment to the Slovenian Code of Criminal Procedure is the introduction of plea bargaining where the prosecutor offers to the defendant a reduced sentence in exchange of his guilty plea. Even though plea bargaining brings obvious advantages to the criminal procedure (the defendant is punished leniently, prosecutor assures the conviction, whereas the court is disburdened of numerous criminal cases and lastly, the elimination of backlog of court cases has benefits for the general public), there are also serious doubts about this method as a proper and just way of solving criminal cases. The article describes some legal, psychological and sociological concerns and the conclusion is reached that without the change of philosophical foundation of Slovenian criminal procedure (from state-oriented crime prosecution to consensual way of solvingcriminal cases) and unless these concerns are adequately addressed, a serious doubt that plea bargaining is appropriate way of solving criminal cases will remain.
Keywords: criminal law; kazensko pravo; plea bargaining; right to fair trial; kazenski postopek; right to public trial; kazniva dejanja; separation of prosecution and adjudication; storilci; krivda; coercion; legitimacy of plea bargaining; priznanje; sodišča; guilty plea; pogajanja; sentence reduction; priznanje krivde; speeding up criminal procedure; pogajanja o priznanju krivde; abolition of criminal procedure; pravica do poštenega sojenja; pravica do javnega sojenja; ločenost funkcije pregona in sojenja; prisila; legitimnost pogajanj o priznanju krivde; znižanje kazni; skrajšanje kazenskega postopka; odprava kazenskega postopka